An evaluation of the Keep Speaking English Program (KSEP) at SK. Paya Resak, Terengganu / Ahmad Saifuddin Che Azhar - Che Azhar, Ahmad Saifuddin (2012)
This study attempts to evaluate the Keep Speaking English Program (KSEP) at Sek. Keb. Paya Resak, Marang, Terengganu. The program was specially designed for the samples as speaking was the toughest skill to be mastered for them. Pupils’ perceptions towards its implementation were identified as well. Apart of that, some teachers’ point of views about the program were also determined through the structured interview done after the program has been completed. For this case study, 32 of the pupils in 6 Arif class were involved as the samples and they have been observed approximately 3 years from 2008 -2011. There were variety of speaking activities implemented during the period of time and most of the were successfully carried out in the classroom. All data obtained from the questionnaires and interview were analysed respectively. The researcher’s observations were also made during the English presentations and other activities in the classroom. Generally, the findings revealed pupils’ positive attitude and perceptions towards KSEP and they had come up with their consensus of supporting the program. The findings suggested that KSEP was a relevant and applicable speaking program that could be organised in the classroom chiefly to improve pupils’ speaking skills. Pupils need to be encouraged to present any suitable tasks individually or in group as they have to increase their confidence levels and communication skills to be better English speakers.